THEEFFECTS OF CURCUMA RHIZOME EXTRACT (Curcuma xanthorrhiza Roxb.)TREATMENT USING VARIOUS DOSES TOWARDS ENDOMETRIAL THICKNESSIN MICE (Mus musculus) TREATED WITH MONOSODIUM GLUTAMATE (MSG) - Inayatilah, Fidia Rizkiah (Journal of Islamic Pharmacy, 2017)
Monosodium Glutamate (MSG) is a food seasoning that is widely used. Consumption of MSG in excessive doses can cause an excess of free radicals in the body that trigger oxidative stress and finally affect the reproductive system hormones. These free radicals can be suppressed by administration of antioxidants. Rhizomes of Curcuma xanthorrhiza extracts containantioxidants and they are widely grown. Theyare used as traditional medicine in Indonesia. This experiment was conducted to investigatewhether rhizomes of Curcuma xanthorrhiza extracts areable to inhibit decreasing endometrial thickness in female mice after receiving orally MSG-treatment.This research adoptedtrue experimental posttest only control group design. It includes 25 mice that were divided into 5 groups: control K1 (CMC) and K2 (MSG), treatment group (MSG and rhizomes of Curcuma xanthorrhiza extracts with dose of 0,4 mg/gBW, 0,8 mg/gBW, 1,2 mg/gBW).In addition, the miceâ€™s endometrium were removed to be subsequently stained using Hematoxillin-Eosin. Thickening of uterus was observed and measured with 40x magnitude using Microphoto Microscope Olympus. Data was analized using One Way ANOVA. The research finally comes with a result showing that there were not any significant differences discovered from the endometrium thickening from the five tested groups (p0,05). Therefore, it is implied that rhizomes of Curcuma xanthorrhiza extracts has no effect on endometrial thickness of uterus by oral MSG-treatment.Â Keywords: MSG, curcuma, endometrium